Becoming professional through dialogical learning: How language activity shapes and (re-) organizes the dialogical self's voicings and positions. (March 2019) - Bertau, Marie-Cécile; Tures, Andrea
Abstract: Combining cultural-historical and dialogical theoretical approaches, we understand language and the self as dialogically related dynamic phenomena. Learning is a dialogic activity shaped by language activity. The specific forms of language that learning activity takes are at the core of our research, leading to a form sensitive concept of professional development. It addresses societal contexts and others as formative and highlights voicings as concrete forms experienced by learning subjects, traceable in the dialogues on the subject's activity. The case study presents the learning activities of early childhood education (ECE) students and teachers within university level training. Video stimulated reflection and interviews were taken as qualitative research strategies to investigate the positioning processes within the dialogical self of students reflecting on their pedagogical practices. With the "Teacher Interaction and Language Rating Scale" (Girolametto et al., 2000) we measured the interaction quality of the language activities in the classroom. The results illustrate the powerful dynamics of the dialogical learning activity: the kind of voicings emerging within the process of acquiring a 'professional self' and their effects on the self-transformative learning process. The ambivalence within learners' self is demonstrated, pointing to a genetic relationship between self-reflective and social positionings within the ECE community.